Urine Characteristics in Pregnant Women with Asymptomatic Bacteriuria: Karakteristik Urine pada Ibu Hamil dengan Bakteriuria Asimptomatik - Zahra Shabrina Wahyu; Nadyah; Najamuddin; Henny Fauziah; Muh. Sadiq Sabri; Darussalam (Prodi Kebidanan Universitas Islam Negeri Alauddin Makassar, 2024)
Introduction, Urinary Tract Infection (UTI) is an infection caused by microorganisms entering the urinary tract through the urethra, progressing to the bladder and sometimes spreading to the kidneys. UTI often occurs during pregnancy with an average incidence rate of around 10%. Asymptomatic bacteriuria and symptomatic UTI (acute cystitis and pyelonephritis) are found in 2-13% and 1-2% of pregnant women, respectively. Therefore, pregnant women should undergo bacteriuria testing early in pregnancy, as UTI is a common cause of inflammation during gestation. Method, This is a quantitative study analyzed using observational analytic procedures with a cross-sectional approach. The sample in this research was collected using accidental sampling method, resulting in a total of 56 samples Result, The research findings indicate that the majority of pregnant women with UTI have leukocyte esterase (+) in 48.2% of cases and positive nitrite in 58.9%. The dominant urine color is yellow (28.6%) with a volume of around 10-20 cc (37.5%). Most UTI patients exhibit turbidity in urine (58.9%), with a pH of 6.0 being the most common at 53.6%. Conclusion, Urine examination results related to color, volume, and pH do not show a significant relationship with the occurrence of UTI. However, turbidity level, leukocyte esterase, and nitrite display a highly significant relationship with UTI incidence. Therefore, these parameters can serve as crucial indicators in the diagnosis and management of UTI in pregnant women.